PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN INOVASI TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA SEBAGAI INTERVENING PADA SD NEGERI DI KOTA CILEGON - Irfan Firdaus, Irfan Firdaus; Sutisna, Sutisna; Komarudin, Mamay (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
An organization's members may be guided in their work by a leader. The principle has the power to influence every student and staff member in the school by his or her charismatic Transformational Leadership style, which in turn may boost the motivation of honorary instructors to do a good job. With motivation as a moderating variable, this research seeks to examine the function of transformational leadership and innovation in raising the performance of honorary teachers in Cilegon City's public elementary schools. Honorary teachers from Cilegon City, Banten Province, who were employed by public elementary schools made up the population studied. There were 153 honorary teacher responders that made up the sample for this research. In order to gather information for this research, a survey was sent out via several social media platforms. This research used SmartPLS v.3.2.8 and the Structural Equation Model (SEM) PLS for analysis. The study's findings indicate that 1) Transformational leadership does have an effect on employee motivation. 2) Transformational leadership has an effect on how well teachers do their jobs. Thirdly, innovation affects intrinsic motivation at work. 4) Innovation has an effect on how well teachers do their jobs. 5) The work motivation of teachers affects their performance in the classroom. 6) As an intermediary, work motivation is a means via which transformational leadership affects teacher performance. 7) As an intermediary, innovation affects teacher performance via work motivation. To sum up, Honorary Teachers' Performance Can Be Boosted Through Transformational Leadership, Innovation, and Work Motivation